2009
DOI: 10.1002/tax.584011
|View full text |Cite
|
Sign up to set email alerts
|

Relationships within Blumea (Inuleae, Asteraceae) and the utility of the 5S­NTS in species­level phylogeny reconstruction

Abstract: In an attempt to improve the phylogenetic resolution in clades of the genus Blumea beyond what could be achieved with sequence data from plastid regions (trnL­F, psbA­trnH) and ITS, the 5S­NTS (non­transcribed spacer) was sequenced as it has been reported to show higher levels of variation than the former regions. 5SNTS yields a tree less resolved than ITS and the plastid regions; the latter markers, moreover, provided more resolution at deeper nodes. When combined with ITS and plastid sequences, 5S­NTS adds v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Because of the variety of its morphology, since the first description of this genus, its phylogenetic analysis and molecular evolution have been vigorously disputed. Over the years, phylogenetic analysis using molecular markers has been widely used to attempt to resolve this dispute (Pornpongrungrueng et al, 2007; Pornpongrungrueng, Borchsenius & Gustafsson, 2009), the results showed that Blumea(included Blumeopsis flava ) is monophyletic, and suggested this genus could be divided into two main clades and one single species, B. balsamifera , which differ in terms of habitat, ecology, and distribution (Pornpongrungrueng et al, 2007). In this study, both nrDNA ITS and cpDNA trnL-F sequences were used to estimate the phylogenetic relationship between the members of this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the variety of its morphology, since the first description of this genus, its phylogenetic analysis and molecular evolution have been vigorously disputed. Over the years, phylogenetic analysis using molecular markers has been widely used to attempt to resolve this dispute (Pornpongrungrueng et al, 2007; Pornpongrungrueng, Borchsenius & Gustafsson, 2009), the results showed that Blumea(included Blumeopsis flava ) is monophyletic, and suggested this genus could be divided into two main clades and one single species, B. balsamifera , which differ in terms of habitat, ecology, and distribution (Pornpongrungrueng et al, 2007). In this study, both nrDNA ITS and cpDNA trnL-F sequences were used to estimate the phylogenetic relationship between the members of this genus.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex and, between taxa, inconsistent molecular evolution of 5S-NTS, the genetic region has by some been regarded as unsuitable for phylogenetic inference (e.g., Sajdak & al., 1998;Pornpongrungrueng & al., 2009). However, the congruence between our 5S-NTS and NRPA2 results supports the utility of this region for phylogenetic inference, at least in Lamium.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description of this genus, its phylogenetic analysis and molecular evolution have been vigorously disputed. Phylogenetic analysis using molecular markers has been widely used to attempt to resolve this dispute; Pornpongrungrueng conducted important research [10,11], whose results showed that Blumea is monophyletic if the genera Blumeopsis Gagnep. and Merrittia Merr.…”
Section: Introductionmentioning
confidence: 99%